2010
DOI: 10.1055/s-0030-1247566
|View full text |Cite
|
Sign up to set email alerts
|

Type-1 Diabetes Induces Depot-Specific Alterations in Adipocyte Diameter and Mass of Adipose Tissues in the Rat

Abstract: Type-1 diabetes (T1D) is a metabolic disorder associated with massive reduction in mass of adipose tissue. Measuring cell diameter, an index of fat metabolism, we determined depot-specific alterations in weight of adipose tissue, fat cell diameter and size heterogeneity and distribution at 5 depots in streptozotocin (STZ)-induced diabetic rats. T1D was induced by a single injection of STZ. Seven days after the injection, fat depots were isolated, weighted, washed and maintained in tissue culture medium. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…This has been attributed to the cell binding characteristics of CP; yet to be determined for adipocytes. Previously we have reported that adipose tissues at diff erent anatomical site may not response equally to the same signal [28] and, therefore, the present data may not be applicable to other fat depots. Regarding the experimental model, cell-cell and cell-matrix interactions which have profound eff ects on cell behavior [29] have been absent in the isolated adipocytes used in the Kitabchi et al experiments.…”
Section: Discussion ▼mentioning
confidence: 59%
“…This has been attributed to the cell binding characteristics of CP; yet to be determined for adipocytes. Previously we have reported that adipose tissues at diff erent anatomical site may not response equally to the same signal [28] and, therefore, the present data may not be applicable to other fat depots. Regarding the experimental model, cell-cell and cell-matrix interactions which have profound eff ects on cell behavior [29] have been absent in the isolated adipocytes used in the Kitabchi et al experiments.…”
Section: Discussion ▼mentioning
confidence: 59%
“…Streptozotocin (STZ) or alloxan-induced diabetic rat or mouse is the most currently used animal model for diabetes. A single intraperitoneal or intravenous injection of STZ is well reported to induce insulin-dependent diabetes in rats (Ghorbani et al, 2010;Ghorbani et al, 2013;Shafiee-Nick et al, 2012b). The histologic feature of islets from the pancreas of diabetic animals is characterized by a severe decrease in the number of islets, inflammation, vacuolation of the islets, and degranulation of the beta cells (Adeyemi et al, 2008;Aralelimath, Bhise, 2012).…”
Section: Pancreatic Beta Cell Degeneration/regenerationmentioning
confidence: 99%
“…Generally, diabetes is classified to two main types: type-1 diabetes (T1D), previously known as insulin-dependent diabetes mellitus, and type-2 diabetes (T2D), formerly called non-insulin-dependent diabetes mellitus. Patients with T1D show a state of insulin deficiency because of severe defect in islet β-cell function while T2D is characterized by a combination of resistance to action of insulin and insufficiency in insulin secretion (Deshpande et al, 2008).Over time, both types of diabetes lead to serious complications in the body, which include nephropathy, retinopathy, neuropathy, dyslipidemia and cardiovascular diseases (Deshpande et al, 2008;Ghorbani et al, 2010). Currently, beside insulin, the most widely used medication A. Ghorbani 414 for diabetes are oral hypoglycemic drugs including insulin sensitizers (biguanides, thiazolidinediones), insulin secretagogues (sulfonylureas, meglitinides), α-glucosidase inhibitors, incretin agonists and dipeptidyl peptidase-4 inhibitors (Lorenzati et al, 2010).…”
mentioning
confidence: 99%